Response of the plant core microbiome to Fusarium oxysporum infection and identification of the pathobiome - Zhiguang Qiu; Jay Prakash Verma; Hongwei Liu; Juntao Wang; Bruna D. Batista; Simranjit Kaur; Arthur Prudêncio de Araujo Pereira; Catriona A. Macdonald; Pankaj Trivedi; Tim Weaver; Warren C. Conaty; David T. Tissue; et al. (Environmental Microbiology, 2022)
Plant core microbiomes consist of persistent key members that provide critical host functions, but their assemblages can be interrupted by biotic and abiotic stresses. The pathobiome is comprised of dynamic microbial interactions in response to disease status of the host. Hence, identifying variation in the core microbiome and pathobiome can significantly advance our understanding of microbial–microbial interactions and consequences for disease progression and host functions. In this study, we combined glasshouse and field studies to analyse the soil and plant rhizosphere microbiome of cotton plants ( Gossypium hirsutum ) in the presence of a cotton‐specific fungal pathogen, Fusarium oxysporum f. sp. vasinfectum (FOV). We found that FOV directly and consistently altered the rhizosphere microbiome, but the biocontrol agents enabled microbial assemblages to resist pathogenic stress. Using co‐occurrence network analysis of the core microbiome, we identified the pathobiome comprised of the pathogen and key associate phylotypes in the cotton microbiome. Isolation and application of some negatively correlated pathobiome members provided protection against plant infection. Importantly, our field survey from multiple cotton fields validated the pattern and responses of core microbiomes under FOV infection. This study advances key understanding of core microbiome responses and existence of plant pathobiomes, which provides a novel framework to better manage plant diseases in agriculture and natural settings.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Herbivore-induced volatile emissions are altered by soil legacy effects in cereal cropping systems - Shealyn C. Malone; David K. Weaver; Tim F. Seipel; Fabian D. Menalled; Megan L. Hofland; Justin B. Runyon; Amy M. Trowbridge (Plant and Soil, 2020)
Aims (main purpose and research question) Soil properties, including microbial composition and nutrient availability, can influence the emissions of plant volatile organic compounds (VOCs) that serve as host-location cues for insect pests and their natural enemies. Agricultural practices have profound effects on soil properties, but how these influence crop VOCs remains largely unknown. The aim of this study was to investigate the effect of agricultural practices on constitutive and herbivore-induced VOC emissions by a major staple crop through soil legacy effects. Methods In a full factorial experiment, we measured VOC emissions by wheat ( Triticum aestivum ) grown in soil inoculum from wheat-fallow or wheat-cover crop rotations that was subjected to feeding by larval Cephus cinctus . Results (main findings) Under herbivory, plants grown in cover crop inoculum emitted greater total VOCs, including higher concentrations of 2-pentadecanone, an insect repellent, and nonanal, a compound important in the recruitment of natural enemies. Plants grown in fallow inoculum showed no differences in emissions whether under herbivory or not. Soil inoculum did not influence VOC emissions of plants in the absence of larval feeding. Conclusions These results suggest that agricultural practices influence crop VOC emissions through soil legacy effects. Additionally, crops grown in wheat-fallow rotations may be less successful recruiting natural enemies of pests through herbivore-induced VOC signaling. Abbreviations Volatile organic compounds (VOCs); herbivore-induced plant volatiles (HIPV); green leaf volatiles (GLVs); northern Great Plains (NGP); wheat stem sawfly (WSS); gas chromatography-mass spectrometry (GC-MS); non-metric multidimensional scaling (NMDS); generalized linear mixed-effects model (GLMM).

Virus species polemics: 14 senior virologists oppose a proposed change to the ICTV definition of virus species - Marc H. V. Van Regenmortel; Hans-Wolfgang Ackermann; Charles H. Calisher; Ralf G. Dietzgen; Marian C. Horzinek; Gunther M. Keil; Brian W. J. Mahy; Giovanni P. Martelli; Frederick A. Murphy; Craig Pringle; Bert K. Rima; Tim Skern; et al. (Archives of Virology, 2013)

A proposal to change existing virus species names to non-Latinized binomials - Marc H. V. Van Regenmortel; Donald S. Burke; Charles H. Calisher; Ralf G. Dietzgen; Claude M. Fauquet; Said A. Ghabrial; Peter B. Jahrling; Karl M. Johnson; Michael R. Holbrook; Marian C. Horzinek; Günther M. Keil; Jens H. Kuhn; et al. (Archives of Virology, 2010)